Response of Groundnut (Arachis hypogaea L.) to Critical Period of Crop-Weed Interference in the West Coast Region of The Gambia - S.A.F. Jallow; F.J. Manneh (European Scientific Journal, ESJ, 2025)
Field trials were conducted in the 2021 rainy season at the National Agricultural Research Institute Banjulinding (NARI Site III) and the Teaching and Research Farm of the University of The Gambia (UTG Faraba Banta) to determine the critical period of crop-weed interference on weed attributes, growth and yield of groundnut varieties. The experiment was conducted in a Randomized Complete Block Design with Nine (9) treatments replicated three times. The treatments tested were as follows:  Weed-free up to 21 DAS, Weed-free up to 42DAS, Weed-free up to 63DAS, Weed-free check, Weed Infestation up to 21DAS, Weed Infestation up to 42 DAS, Weed Infestation up to 63 DAS, Weedy check. The groundnut variety used as a test crop was Fleur 11. The results revealed that weed-free check (75 DAS) consistently recorded the highest weed control efficiency and lowest weed infestation, weed density, and weed dry weight in both locations. The weedy check had the lowest weed control efficiency in both locations. Similarly, the weed-free check consistently had a positive effect on growth and yield characters. The critical period for crop-weed interference in the groundnut variety tested was observed to be between 21 DAS to 63 DAS.  It could be concluded that weed-free check followed by weed-free up to 63DAS and weed-free up to 42 DAS had led to the production of the highest pod and kernel yields of groundnut.